Syriac Love Charms: Part II. The Prayer-Type - Cherkashina, Anna; Lyavdansky, Alexey (2022)
The first part of our inquiry on Syriac love charms was devoted to the recipe-type charms. This article edits four more Syriac love charms, which we attribute to the so-called prayer-type. The special features of this type of Syriac love charms are addressed and compared with that of the recipe-type texts, edited in Part I. The commentary to each text provides philological notes and parallels, both from within and outside of Syriac magical tradition.
Keywords: Aramaic; medieval and modern Syriac manuscripts; erotic magic; magic books; Magic; Eastern Christianity; Syriac charms